The Impact of Leader Proactivity on Follower Proactivity: A Chain Mediation Model - Zhang, Kaixin; Cui, Zilong (Frontiers in Psychology, 2022)
This study aims to explore the linking mechanisms underlying the relationship between leader proactivity and follower proactivity. Drawing on social learning theory, the present research investigates the effects of leader proactivity on follower proactivity by developing a chain mediation model. An analysis of three-wave lagged data (N = 575) on 575 employees of six firms in China shows that leader proactivity is positively related to follower proactivity and that employees’ role breadth self-efficacy (RBSE) and felt responsibility for constructive change (FRCC) mediate this relationship. The analytical results also show that leader proactivity facilitates follower value congruence, which in turn enhances followers’ RBSE and FRCC and ultimately promotes followers’ proactivity. The results extend the current proactivity literature and fill the research gap by investigating the relationship between leader proactivity and follower proactivity. The current study also contributes to the literature by identifying the mediating mechanism of the “can do” and “reason to” mechanisms that link leader proactivity to follower proactivity.